IMPLEMENTASI PROGRAM TAHFIDZ AL-QUR’AN DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA - Adi Sulistyo Wibowo; Joko Subando (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Character education is a form of effort to change the nature, morals, character of a person to become a better person based on religious rules. Character cultivation needs to be instilled early, one of which is through daily habituation. Character planting aims to form the next generation of the nation that has a good personality, and form a generation that is ready to face the times. This journal will discuss the theory of the implementation of the Qur'an tahfidz program in improving students' religious character. There are three phases of implementation, namely, planning, implementation, and evaluation. The Tahfidz Al-Qur'an program is a memorization activity with strong memorization of the lafadz or its meaning so that the Al-Qur'an lives in the heart at all times making it easier to practice it. This research uses the literature review method to produce theories and conclusions from relevant articles and scientific journals. There are three phases of implementation, namely, planning, implementation, and evaluation. Religious character is behavior and morals in accordance with what is taught in education. Religious character has several indicators, namely honesty, discipline, and social care.